أحكام الزواج والطلاق في بلاد الرافدين - بوطيب, مفيدة (جامعة الوادي - University of Eloued, 2023)
تتجسد الحياة الاجتماعية في بلاد الرافدين وبصفة خاصة الأحوال الشخصية فيما يخص الزواج والطلاق من حيث العادات والتقاليد والقوانين التي عالجتها فيما يخص الزواج الركن الأساسي لتكوين الأسرة، ونظرا لأهمية الزواج في مجتمع الرافدين حرص المجتمع على قيام صفة العلاقة، وكان الزواج من زوجة واحدة هو السائد إلا أن هناك حالات تسمح بتعدد الزواج في حالة مرض أو عقم الزوجة واتخاذ جارية من أجل المتعة. وكما أن للزواج أحكاما يجب أن تتم لكي يصبح الزواج صحيحا، كإرضاء أولياء الزوجين وكتابة عقد الزواج، كما قد يحصل خلاف بين الزوجين فيقع الطلاق وذلك بإنهاء العلاقة، وهناك أسباب وحالات وآثار تترتب على الطلاق. Summary Social life isembodied in Mesopotamia, especiallypersonalstatuswith regard to marriage and divorce, in terms of customs, traditions, and lawsthatdealtwithit in relation to marriage, the basic pillar of family formation, and given the importance of marriage in Mesopotamian society, society waskeen to establish a relationship, and marriage to one wifewasprevalentexcept That there are cases thatallowpolygamy in the event of illness or sterility of the wife and taking a slave girl for the sake of pleasure. And just as marriage has provisions that must take place in order for the marriage to becomevalid, such as satisfying the parents of the spouses and writing the marriagecontract, just as a disputemayoccurbetween the spouses, and divorce takes place by ending the relationship, and there are reasons, cases, and effectsthatresultfrom divorce.
مذكرة ماستر تاريخ تخصص تاريخ حضارات قديمة